Personal and professional development through sustainable partnerships in education Serbian experiences from the I-TAP-PD Erasmus+ project - Koruga, Nikola; Đokić, Dunja; Krsmanović Tasić, Sanja (Education & Theatre, 2023)
The aim of this research is to evaluate how the partnership between teachers and artists was built in the context of Serbia. In conducting it, we sought answers to the following research question: What was the role of I-TAP-PD in the personal and professional development of teachers and artists in Serbia? It is based on the phenomenological theory of reflection in action. Research participants include three teacher-artist pairs. The residencies were delivered between August 2021 and June 2022. The data was collected with pre-residency questionnaires, reflective journals, classroom observation, post-residency group interviews. All qualitative data was analysed using thematic analysis. The results show that artists and teachers, in terms of sustainable partnership in researched practices in Serbia, identified the understanding of the “other“ as the most important aspect of the process of learning and teaching. In this endeavour, professionals developed high levels of empathy and their self-esteem notably increased.